2020
DOI: 10.1386/ajpc_00017_1
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous approaches to the past: ‘Creative histories’ at the Hyde Park Barracks, Sydney

Abstract: This article discusses a recent art project created by the Wiradjuri and Kamilaroi artist Jonathon Jones, which was commissioned to commemorate the opening of the revitalized Hyde Park Barracks in Sydney in early 2020. Jones’ work involves a dramatic installation of red and white crushed stones laid throughout the grounds of the barracks, merging the image of the emu footprint with that of the English broad convict arrow to ‘consider Australia’s layered history and contemporary cultural relations’. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…us far, for example, my consultation with elders has revealed that the bloom of Warra Garria, grey spider grevillea, indicated when it was time to hunt for shell sh, while the purple owers of the Warraburra, false sarsaparilla, signalled when it was time to sh for fat bream in the saltwater streams. 68 e thorny mountain devil, lambertia formosa, which Aesi also painted, was one of many that provided sustenance for it released a sweet honey nectar that made for a refreshing energy drink when it was swished in water. 69 In contrast, the Nirra Nirra or Pokulbi, also known as Flax Lily or Dianella, produced a purple berry that was eaten and used for dying baskets.…”
Section: What?mentioning
confidence: 99%
“…us far, for example, my consultation with elders has revealed that the bloom of Warra Garria, grey spider grevillea, indicated when it was time to hunt for shell sh, while the purple owers of the Warraburra, false sarsaparilla, signalled when it was time to sh for fat bream in the saltwater streams. 68 e thorny mountain devil, lambertia formosa, which Aesi also painted, was one of many that provided sustenance for it released a sweet honey nectar that made for a refreshing energy drink when it was swished in water. 69 In contrast, the Nirra Nirra or Pokulbi, also known as Flax Lily or Dianella, produced a purple berry that was eaten and used for dying baskets.…”
Section: What?mentioning
confidence: 99%